Managing conflict with peers - Cartwright, Talula (Center for Creative Leadership, 2003)
"Aimed at managers and executives who are concerned with their own and others' development, each guidebook in this series gives specific advice on how to complete a developmental task or solve a leadership problem."
Includes bibliographical references. - Print version record
Keywords: Conflict management; Interpersonal conflict; Organizational effectiveness; Leadership; Communication in management; Organizational behavior; Gestion des conflits; Conflit interpersonnel; Efficacité organisationnelle; BUSINESS & ECONOMICS; Motivational; BUSINESS & ECONOMICS; Mentoring & Coaching